Analysis Of Marketing Mix And Ahlussunnahwaljamaah's Label On The Decisions Of College Students At IUQI Bogor: Introduction, theoretical study, research methods, results and discussion, bibliography - Roisiyatin; Warisa, Walma (UPT Penerbitan Universitas Jember, 2025)
This research aims to analyze the influence of the marketing mix (7P) and the Ahlussunnahwaljamaah (Aswaja) label on students' decisions to study at the Ummul Quro Al Islami Institute (IUQI) Bogor. Using a quantitative approach with explanatory research, this research involved a population of 1,613 IUQI Bogor students with a sample of 94 respondents selected using a simple random sampling technique. Primary data was collected using a questionnaire and analyzed using multiple linear regression. The research results show that partially, physical evidence and the Aswaja label have a significant effect on student decisions, while the product, promotion, price, people, place and process variables do not have a significant effect. However, simultaneously, all marketing mix variables and the Aswaja label have a significant positive effect on student decisions with a coefficient of determination value of 78.4%. The implication is that IUQI Bogor needs to maintain and improve the quality of its physical facilities and strengthen the Aswaja label as a differentiation in its marketing strategy, while continuing to optimize other marketing mix elements to increase the institution's attractiveness.